Inondations, aide alimentaire, et marchés alimentaires au Bangladesh: répondre à une urgence nationale - del Ninno, Carlo; Dorosh, Paul A.; Smith, Lisa C.; Roy, Dilip K. (International Food Policy Research Institute, 2003)
The synergy between food assistance and market development contributed to avoiding a food-price crisis. In addition to being well targeted, timely, and efficiently administered, food assistance needs to reach the vulnerable in sufficient amounts and maintain a long enough presence to address their needs in the medium as well as the short term.